2022
DOI: 10.1007/s00248-022-02038-0
|View full text |Cite
|
Sign up to set email alerts
|

Consistency and Variation in the Kelp Microbiota: Patterns of Bacterial Community Structure Across Spatial Scales

Abstract: Kelp species are distributed along ~25% of the world's coastlines and the forests they form represent some of the world's most productive and diverse ecosystems. Like other marine habitat-formers, the associated microbial community is fundamental for host and, in turn, wider ecosystem functioning. Given there are thousands of bacteria-host associations, determining which relationships are important remains a major challenge. We characterised the associated bacteria of two habitat-forming kelp species, Laminari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 77 publications
2
6
0
Order By: Relevance
“…Those taxa were also found on the meristem part of L. digitata (Ihua et al, 2020) and on the blade of L. setchellii (Lemay et al, 2021), Taonia atomaria (Paix et al, 2021), and U. lactuca (Comba González et al, 2021). Our results are furthermore consistent with the core microbiota found in S. latissima and L. hyperborea in the United Kingdom (King et al, 2022). Granulosicoccus sp.…”
Section: Discussionsupporting
confidence: 88%
“…Those taxa were also found on the meristem part of L. digitata (Ihua et al, 2020) and on the blade of L. setchellii (Lemay et al, 2021), Taonia atomaria (Paix et al, 2021), and U. lactuca (Comba González et al, 2021). Our results are furthermore consistent with the core microbiota found in S. latissima and L. hyperborea in the United Kingdom (King et al, 2022). Granulosicoccus sp.…”
Section: Discussionsupporting
confidence: 88%
“…lactuca (Comba González et al, 2021). Our results are furthermore consistent with the core microbiota found in S. latissima and L. hyperborea in the United Kingdom (King et al, 2022).…”
Section: /32supporting
confidence: 89%
“…Yet, within this variability a suite of taxa frequently found on macroalgal surfaces is emerging across studies, including Saprospiraceae, Granulosicoccus, and Flavobacteria [34][35][36]. Earlier studies reported a handful of core bacterial taxa consistently associated with particular populations in a few macroalgal species, including Kelp [37], Agarophyton vermiculophyllum [38], Fucus vesiculosus [28], Ulva australis [39] and Ascophyllum nodosum [40]. However, these studies were limited in scope, focusing on one location at one point in time, often without corresponding sampling of the macroalgae' environment.…”
Section: Introductionmentioning
confidence: 99%